16+7b-5b=11b-3-b

Simple and best practice solution for 16+7b-5b=11b-3-b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16+7b-5b=11b-3-b equation:



16+7b-5b=11b-3-b
We move all terms to the left:
16+7b-5b-(11b-3-b)=0
We add all the numbers together, and all the variables
7b-5b-(10b-3)+16=0
We add all the numbers together, and all the variables
2b-(10b-3)+16=0
We get rid of parentheses
2b-10b+3+16=0
We add all the numbers together, and all the variables
-8b+19=0
We move all terms containing b to the left, all other terms to the right
-8b=-19
b=-19/-8
b=2+3/8

See similar equations:

| 12(x–2)+3x=0.5(x+6)+2 | | (50-x)+(2x+40)+80=180 | | 50-x+2x+40=100 | | 6m=14m-26 | | 9+k=28 | | 50=-3x-9 | | 7/3-3/x+5=19/12 | | 0.13x+0.03(60000-x)=5000 | | 100x=65•475 | | 3(x-1.8)=2x+.1 | | h/3-8=10 | | –5p=–5p+4 | | (x^2)+2.2x-42.35=0 | | 5+(12/(x-3))=9 | | 9a–2a=21 | | m-11=0 | | r+–8=–1 | | 19j–18j=12 | | 69*x+9*x=320000 | | x3-2=x6+4 | | 5.1g+4=3.1g+16 | | 11=x+16 | | 2(y+3)=5(y-6) | | 8y+7=5y-11 | | 7w^2-3w-39=0 | | 13=4n | | -26=x-19 | | -34=b-18 | | -34=n-18 | | (1+4p)=(4p-1)(p+2) | | 0.2x+5=0.5x+2 | | -10-(-6x)=-1x |

Equations solver categories